Educational Strategies for Increasing Cardiopulmonary Resuscitation Ability in Lay Person Scoping Review - Lisajidin, Muhamad; Putra, Kuswantoro Rusca; Yuliatun, Laily (Jurnal Health Sains, 2024)
Objectives: Cardiac arrest can be experienced by anyone and evenincidentcardiac arrestdo not recognizeplace andtime.This article aims to maximize cardiopulmonary resuscitation training strategies with a focused review of articles on CPR training strategies for lay people. Methods:In this Scooping Reviewan international journal search was conducted on the topic by browsing the online databases of ProQuest, EBSCO, and ScienceDirect, using the keywords “strategy” AND “education” AND “improvement” AND “ability” AND “citizen” OR “lay person” OR “person layman” AND “bystander” AND “CPR” OR “cardiopulmonary rescucitation”. Literature was selected based on inclusion criteria, i.e. according to topic, full text articles, English, quantitative methods, experiments, CPR educational themes, full text, open access and articles published in the last 10 years (2013-2023), while the sample exclusion criteria were research thattherein isinvasive actions and there areparticipants with a background in nursing or other health professions. The stages of searching and selecting journal articles are adapted from the PRISMA flowchart Results:At initial disbursement, 858 articles were obtained with 7 studies that met the inclusion criteria. Articles were obtained using a pre-post intervention design (1 article), a prospective cohort intervention (3 articles), a cross-sectional experimental study (1 article), a retrospective design and qualitative methods (2 articles). Based on the articles obtained, there are 3 articles on educational strategies to improve cardiopulmonary resuscitation abilities in ordinary people, which include education, simulation, team, and comprehensive programs. Conclusion:Appropriate media can have a major impact on improving knowledge, attitudes and skills to performing CPR